2019
DOI: 10.1158/1541-7786.mcr-18-1195
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutation by CRISPR System Enhances the Malignant Potential of Colon Cancer

Abstract: Tumor protein p53 (TP53) mutation is a well-known occurrence at the late phase of carcinogenesis during the adenoma-carcinoma sequence of a sporadic colon cancer. Although numerous reports about clinical information of the patients with colon cancer have suggested that TP53 mutation might be related to various types of malignant potential, the direct effects of this mutation on the malignant potential of colon cancer remain unknown. Notably, no previous report has described a relationship between TP53 mutation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…UBR5 has been reported to be a regulator of the p53 protein, a tumor suppressor 25,26 . Compromised p53 expression and loss of function mutations in TP53 contribute to the generation of cancer stem cells (CSCs) [27][28][29] . Consistently, we observed an elevated p53 protein level in ID8/ Ubr5 -/tumor compared to WT tumor, whereas in UBR5overexpressing ID8/GFP tumor, p53 level was decreased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…UBR5 has been reported to be a regulator of the p53 protein, a tumor suppressor 25,26 . Compromised p53 expression and loss of function mutations in TP53 contribute to the generation of cancer stem cells (CSCs) [27][28][29] . Consistently, we observed an elevated p53 protein level in ID8/ Ubr5 -/tumor compared to WT tumor, whereas in UBR5overexpressing ID8/GFP tumor, p53 level was decreased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high-risk group showed high TP53 mutation frequency whether in TCGA-LUAD or GSE72094. TP53 mutation is an adverse prognostic factor for advanced non-small-cell lung cancer (NSCLC) ( Jiao et al, 2018 ) and a hallmark event of advanced sporadic colon cancer ( Watanabe et al, 2019 ). Moreover, Haupt et al (2019) found that high TP53 frequency and P53 network dysregulation trigger low survival rate of male cancer patients in North America.…”
Section: Discussionmentioning
confidence: 99%
“…2019) e a proteĂ­na TP53 no cĂąncer de cĂłlon (WATANABE et al, 2019) tiveram mutaçÔes induzidas por CRISPR/Cas9 a fim de avaliar a progressĂŁo tumoral, que foi acentuada e, no caso de TP53, ainda houve aumento da quimiorresistĂȘncia (WATANABE et al, 2019).…”
Section: Discussionunclassified